2007
DOI: 10.1093/her/cyn029
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation results from a school- and community-linked intervention: the Trial of Activity for Adolescent Girls (TAAG)

Abstract: Process evaluation is a component of intervention research that evaluates whether interventions are delivered and received as intended. Here, we describe the process evaluation results for the Trial of Activity for Adolescent Girls (TAAG) intervention. The intervention consisted of four synergistic components designed to provide supportive school- and community-linked environments to prevent the decline in physical activity in adolescent girls. Process evaluation results indicate that the intervention componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
78
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 24 publications
3
78
2
Order By: Relevance
“…The majority of instructors adhered to the manual in the earlier sessions, but as the intervention progressed they began to develop sessions based on what the girls wanted to cover. Fidelity was slightly lower than has been reported in other studies; 90,95 however, this was expected to an extent, as instructors were encouraged to be autonomy-supportive and responsive to the needs of the girls.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The majority of instructors adhered to the manual in the earlier sessions, but as the intervention progressed they began to develop sessions based on what the girls wanted to cover. Fidelity was slightly lower than has been reported in other studies; 90,95 however, this was expected to an extent, as instructors were encouraged to be autonomy-supportive and responsive to the needs of the girls.…”
Section: Discussionmentioning
confidence: 58%
“…Girls have previously reported that they would be more likely to attend a session if their friends encouraged them to go. 19 In the current study, girls described enjoying 39,94,95 Aspects that were enjoyed by girls included learning new dance material, group work and dancing to current music. The perceived levels of exertion for dance sessions were low, similar to findings from the BGDP feasibility trial in which average exertion was 3.5 (out of 10).…”
Section: Discussionmentioning
confidence: 78%
“…The barriers and facilitators documented during the HEALTHY study are similar to those reported in similar school-based intervention studies promoting physical activity and/or nutrition, including Lifestyle Education for Activity Program (LEAP), Middle-School Physical Activity and Nutrition (M-SPAN), Pathways, Peers Running Organized Play (PROPS), Physical Activity Across the Curriculum (PAAC), and Trial of Activity for Adolescent Girls (TAAG) [18][19][20][21][22][23][24][25]. Common facilitators reported include interest and support from various school members (i.e., school board member, school administrators, school office staff, teachers, students, and parents), schools that had made physical activity and nutrition a priority prior to study, schools already implementing practices and strategies similar to intervention components, teachers collaborating with one another during implementation, and teachers and food service staff who were motivated and actively engaged in intervention implementation [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 58%
“…These barriers include financial constraints in the school food service system, inadequate facility space to implement activities or store equipment, lack of school personnel to deliver intervention components, and faculty and staff turnover [18][19][20][22][23][24]. Other barriers related to logistical issues in terms of food and beverage ordering problems, school districts with highly centralized food service systems impeding individual school nutrition changes, school scheduling problems, and teacher time constraints [18][19][20][22][23][24][25]. Some teachers reported being unable to implement intervention components due to school prioritization of nonhealth-related curricula and standardized testing requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation